Treatment of Superficial Cutaneous Vascular Lesions: Experience with the Long-Pulsed 1064 nm Nd:YAG Laser - Kemal Ozyurt; Emine Colgecen; Halit Baykan; Perihan Ozturk; Mehmet Ozkose (The Scientific World Journal)
Recent published studies evaluating the long-pulsed 1064 nm Nd:YAG laser for superficial cutaneous vascular lesions have limited subjects and optimal treatment parameters have not been established. To determine the efficacy and safety of the long-pulsed 1064 nm Nd:YAG laser on superficial cutaneus vascular lesions and analyse retrospectively our experience of a 3-year period are the aims of this study. Over the 3-year period, 255 patients were treated [189 female and 66 male; median age 35 (range 7–65) years; Fitzpatrick skin types II-V]. Twenty-six patients with spider angioma, 130 with facial telangiectasia, and 99 with leg telangiectasia were treated. A long-pulsed 1064 nm Nd:YAG laser was used. A test dose was performed at the initial consultation and thereafter patients were reviewed and treated at 4-week intervals for 5 months. Of those patients who completed treatment and followup, 26/26 (100%) of spider angiomas, 125/130 (97%) of facial telangiectasia, and 80/99 (80,8%) of leg telangiectasia markedly improved or cleared. We suggest that the long pulsed Nd:YAG laser is a safe and effective treatment for common superficial cutaneous vascular lesions. However, it is not the first choise to use to treat superficial vessels on the face where depth is not the concern.